2017
DOI: 10.1016/j.ejso.2017.05.023
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pre- and post-operative weight loss and body mass index on prognosis in patients with oesophageal cancer

Abstract: Post-operative weight loss and low BMI at 6 months post-surgery are independent markers of poor prognosis in patients who undergo surgery for oesophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 40 publications
(38 reference statements)
4
34
0
Order By: Relevance
“…Patients with preoperative weight loss had a 19% higher risk of death (HR=1.19, 95%CI: 1.07-1.33, P=0.002) and a 13% higher risk of disease progression than those without weight loss. The previous studies also showed that preoperative weight loss was significantly associated with poor prognosis [11][12][13], which is consistent with our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients with preoperative weight loss had a 19% higher risk of death (HR=1.19, 95%CI: 1.07-1.33, P=0.002) and a 13% higher risk of disease progression than those without weight loss. The previous studies also showed that preoperative weight loss was significantly associated with poor prognosis [11][12][13], which is consistent with our study.…”
Section: Discussionsupporting
confidence: 93%
“…Hynes' and Van' studys showed that preoperative weight loss of >10% was a potential risk factor for the prognosis of patients undergoing radical esophagectomy. And in Yu's cohort of patients receiving adjuvant chemotherapy after radical esophagectomy indicated that the greater the weight loss, the worse the prognosis [11][12][13]. On the contrary, other studies have suggested that weight loss is not a reliable independent prognostic factor [14].…”
Section: Ivyspringmentioning
confidence: 99%
“…were associated with poor prognosis [29,30]. This phenomenon, well known in cardiovascular 13 literature, is called the obesity paradox [31].…”
Section: Post-diagnosis Statin Usementioning
confidence: 99%
“…Esophagectomy or neoadjuvant therapy followed by esophagectomy is the critical therapy for this malignant tumor . Postoperative weight loss is a common problem in patients with esophageal cancer, and severe weight loss (SWL) is closely related to poor prognosis . However, the degrees of postoperative body weight changes and the risk factors for SWL have not been identified .…”
Section: Introductionmentioning
confidence: 99%
“…2 Postoperative weight loss is a common problem in patients with esophageal cancer, and severe weight loss (SWL) is closely related to poor prognosis. 3,4 However, the degrees of postoperative body weight changes and the risk factors for SWL have not been identified. 5,6 The purpose of this study was to prospectively observe body weight changes in patients who underwent minimally invasive McKeown esophagectomy (McKeown-MIE) to explore the regularity of body weight changes and to analyze the risk factors leading to SWL.…”
Section: Introductionmentioning
confidence: 99%